Effect of the Ecological Methods on the Surface Modification of the Kenaf Fibers - KOÇAK, EMİNE DİLARA; MISTIK, SÜLEYMAN İLKER (KAUNAS UNIV TECH, 2016)
Kenaf is a biodegradable and environmental friendly bast fibre. The most rapidly expanding application field for kenaf fibre is composites as reinforcing material. In this study four different chemical treatments were applied to kenaf fibre by using conventional, ultrasonic and microwave methods. Weight loss, tensile strength, elongation properties, morphological characteristics (SEM) and FTIR analysis of the treated kenaf fibre were carried out. Valuable results were obtained from formic acid and acetic acid treatments of kenaf fibre by ultrasonic and microwave methods. The reasons for the ultrasonic and microwave processes to be successful are the strength achieved by sonication and microwave.
Keywords: bio fibre; surface treatment; kenaf fibre; ultrasonic energy; microwaves; ULTRASONIC ENERGY; FLAX FIBER; MECHANICAL-PROPERTIES; CHEMICAL TREATMENTS; THERMAL-PROPERTIES; ALKALI TREATMENT; COMPOSITES; JUTE; ACETYLATION